The Process of Public Policy Awareness and Public Participation in Loei Province. - Wongwarunyoo, Teerawat (Journal of Humanities and Social Sciences Loei Rajabhat University, 2024)
The objectives of this research were 1) to study the level of public policy interest of the people in Loei province, 2) to study the process of public policy perception of the people in Loei province, and 3) to study the guidelines of the people in Loei province. To participate in the public policy process. This research is a mixed methods research between qualitative research and quantitative research by collecting data from voters in Loei province. A total of 465 people were sampled from the questionnaire. 400 people using statistics for analysis. Samples were collected from 65 interviews to identify findings and correlate with relevant theories. The study found that 1) 20.5 percent of people access public policy twice a week, with the most online channels (35.5 percent), and television being the most appropriate and effective channel. In public policy awareness 34.8 percent 2) Level of public policy awareness The 12 main policies were moderate, with an average of 3.16. The average is 3.50. The policy with the lowest level of awareness is the 4th main policy: Building Thailand's role on the world stage. The average is 2.92 3) Level of understanding of public policy The 12 main policies were moderate, with an average of 3.04. The policy with the lowest level of understanding was Key Policy 4, Building Thailand's Role on the World Stage, and Core Policy 6, Economic Area Development and Regional Prosperity, with an average of 2.83 4) People will participate in public policy activities and express themselves by talking in friends or family and kinship and publicizing government policies through social media channels so that others can better understand and express themselves by voting for members of the House of Representatives. By supporting political parties that set their favorite policies. But if it is public policy that is not favored, it will refuse to participate. They also explain the reasons why they don't like the policy to others in order to be amenable to it through discussions or online. When irregularities in public policy or irregularities from policy implementation from government agencies are found. Complaints will be made directly through government agencies and coordinated through village leaders for advice or advice on next steps or complaints through online channels of relevant agencies. To participate in public policy making, they participate through social media expression and through organized government agencies or government officials, such as through village chiefs or village leaders